Study on InSAR deformation information extraction and stress state assessment in a railway tunnel in a plateau area - Lyu, Baihang; Liu, Bo; Xie, Binfu; Xiao, Hairong; Liu, Xing; Zhang, Ziwen; Li, Yang; Huang, Xiameng; Shi, Fangzhe (Frontiers in Earth Science, 2024)
The study proposes a method for evaluating stress distribution in high-altitude Tibetan plateau railway tunnels using high-precision radar satellite time-series Interferometric Synthetic Aperture Radar (InSAR) technology. This method is used to effectively monitor and prevent geological hazards during the construction process, as it serves as a component of advanced geological prediction and surrounding rock deformation monitoring technology for high-altitude tunnels, particularly in the Dongelu Tunnel of the China-Tibet Railway. The study uses Time-Series InSAR (TS-InSAR) to obtain deformation information for the Dongelu Tunnel area between 2022 and 2023 from Sentinel-1A orbit images. This quantitatively investigates the upper mountain body and Line of Sight (LOS) direction along the tunnel. The deformation characteristics are correlated with high-frequency and high-precision automated vertical displacement monitoring results, determining the spatiotemporal distribution of tunnel deformation. A model for the vertical stress state of the Dongelu Tunnel under loading near the entrance and evaluates its health status was established. Results show that the surface deformation of the mountain above the tunnel axis develops slowly and is relatively small, with a maximum vertical deformation rate of 1-3 mm/year. The average stress on the tunnel arch is 5.54 MPa, with a fluctuation range of 0.01 MPa. Temporal changes in various parts of the tunnel are periodic, with maximum fluctuations observed in December 2022. The study reveals inconsistent surface settlement of the tunnel arch and the mountain above it, causing minor vertical stress changes. As the tunnel construction progresses, vertical stress variation shows periodicity due to initial imbalance in internal stress within the mountain. Stress fluctuations near the tunnel entrance occur during the initial excavation phase, gradually diminishing as the project progresses and internal stress stabilizes. The proposed tunnel monitoring and stability assessment method can reduce its impact on engineering construction and provide guidance for advanced geological prediction of tunnels.